Enhanced tetracycline removal using membrane-like air-cathode with high flux and anti-fouling performance in flow-through electro-filtration system. (1st October 2022) - Song, Xiangru; Jo, ChungHyok; Zhou, Minghua
Highlights: Membrane-like cathode improved performance of electro-filtration system. Tetracycline removal and anti-fouling properties was improved by polyaniline. Fenton-like effect of polyaniline excited process of H2 O2 to OH. Tetracycline (0.5 mg L −1 ) removal in river background was near 100%. ABSTRACT: The membrane-like air-cathodes modified with different polyaniline were prepared using phase inversion method, which possessed dual functions of interception and electrochemical degradation, and showed good conductivity (15.9 ± 0.4 to 25.7 ± 0.5 mS cm −1 ) and porosity (77.0 ± 0.1 to 87.8 ± 0.1%) compared to the unmodified control one (13.2 ± 0.5 mS cm −1, and 63.1 ± 0.7%). At tetracycline 50 mg L −1, the cathode with 25 wt% polyaniline exhibited the highest rejection rate and final removal (71.1% and 92.9%, 35.9% and 31.4% higher than the control), the highest water flux recovery (97.9%), and the lowest attenuation of porosity and conductivity. The modified cathode also showed an autocatalytic effect on H2 O2, an obvious · OH peak appeared on the electron paramagnetic resonance curves. It also had good anti-fouling performance because it exhibited a high durability (the final removal was decreased by 4.0% after 15 cycles) with a long service life of 124 periods (372 h, 15.5 d). The tetracycline (0.5 mg L −1 ) removal in the river background was near 100%, and the chemical oxygen demand removal was 91.9%, supporting that it was suitable for treating antibiotics in natural water without adding agents but only for electricity consumption. Graphical abstract: Image, graphical abstract